Memory T cells: strategies for optimizing tumor immunotherapy - Liu, Qingjun; Sun, Zhongjie; Chen, Ligong (Protein & cell, 2020)
Several studies have demonstrated that memory T cells including stem cell memory (Tscm) T cells and central memory (Tcm) T cells show superior persistence and antitumor immunity compared with effector memory T (Tem) cells and effector T (Teff) cells. Furthermore, the Tcm/Teff ratio has been reported to be a predictive biomarker of immune responses against some tumors. Thus, a system-level understanding of the mechanisms underlying the differentiation of effector and memory T cells is of increasing importance for developing immunological strategies against various tumors. This review focuses on recent advances in efficacy against tumors, the origin, formation mechanisms of memory T cells, and the role of the gut microbiota in memory T cell formation. Furthermore, we summarize strategies to generate memory T cells in ( ex ) vivo that, might be applicable in clinical practice.